Understanding gender differences in maize productivity among smallholders in central Uganda: a total factor productivity approach - Dick Chune Midamba; Accram Jjengo; Kevin Okoth Ouko (Discover Agriculture)
Abstract Despite women’s dominance in maize production in Uganda, there have been reported cases of food insecurity among the female-headed households. In this study, we assessed gender disparities in maize productivity and the determinants of maize productivity among the male and female-headed households using cross-sectional data collected from 396 farmers in central Uganda. Data analysis was done using Total Factor Productivity and Tobit regression model. The findings suggested that female-headed households were 24.26% less productive than their fellow male-headed counterparts. The results from econometric analysis showed that education, farm size, input access, non-farm income and access to market information had positive and significant effect of maize productivity while household size, market distance and group membership had negative significant effects on maize productivity among the female-headed households. On the other hand, age, input access, sub-county and road access had positive influence on maize productivity while household size had a negative effect on maize productivity among the male-headed households. From the results, the study concluded that there is gender disparity among the male and female-headed households. The findings suggest that subsidizing farm inputs to smallholder farmers while training them through extension services could help to bridge gender gaps in maize productivity among the female-headed households.